Hearts Strangely Warmed (and Cooled): Emotional Experience in Religious and Atheistic Individuals - Burris, Christopher T. (The international journal for the psychology of religion, 2011)
In light of neurophysiological evidence suggesting a link between hemispheric dominance and religious preference, three studies tested whether atheists and religious individuals process emotions differently. Suggestive of right-hemispheric dominance, individuals who identified with religion reported more intense positive emotions associated with a recalled love experience (Study 1), greater sadness in immediate response to reading a tragic news story (Study 2), and more vivid recall of the subjective details of either their most recent birthday or an existential crisis (Study 3). They also reported greater alexithymia compared to atheists. Overall, agnostic/no religion individuals averaged in between these two groups. The results suggest that, relative to atheists, religious individuals have more accessible yet undifferentiated emotions, which may perhaps serve as raw materials for religious experience.